Mini percutaneous nephrolithotripsy for pediatric kidney stone using 1.5mm probe size shock pulse lithotriptor: A case report - Muhammad Aldito Rivaldi; Zola Wijayanti; Vicky Ferdian (Urology Case Reports, 2023)
The recent development of mini-PCNL technique, allows tract formation with minimal damage to the renal parenchyma in pediatric patients. This report describes our preliminary findings with mini-PCNL using a 1.5-mm probe-size shock pulse lithotriptor. A 11-year-old child presented with multiple small inferior calyceal calculi. The patients were placed in Bartz flank-free modified supine position and underwent mini PCNL. The stone was fragmented using a 1.5-mm probe shock pulse lithotripter and fragments were suctioned out through the hollow probe. Our experience suggests that using a shock pulse lithotripter on a mini-PCNL to treat renal stones in children is both safe and effective.